Located institutions: neighborhood frames, residential preferences, and the case of policing - Bell, Monica C. (The American journal of sociology, 2020)
How do parents weigh police presence and police activity in their assessments of a neighborhood’s suitability for raising children? How do place-bound institutions relate to neighborhood frames? This article introduces located institutions as a way of articulating how certain institutions—here, the police—become a lens through which parents make meaning of places and thus express preferences for particular neighborhoods or communities. By drawing from 73 interviews with a diverse sample of parents in Cuyahoga County, Ohio, this article shows how parents draw on their perceptions of the police as an attractive amenity or a public nuisance as a way of articulating neighborhood frames and making sense of their residential preferences. More broadly, this article envisions the perception of institutions as a key mechanism that shapes neighborhood frames and residential preferences.